Gamification and player type: Relationships of the HEXAD model with the learning experience - Silvia Sipone; Victor Abella; Marta Rojo; José Luis Moura (Journal of New Approaches in Educational Research)
Abstract Gamification is a widely utilised educational tool designed to promote specific behaviours. An effective gamification design must consider users’ experiences and perceptions to enhance engagement and participation. This research is part of a broader study that develops gamified activities to teach primary school pupils about sustainable mobility. The study investigates the relationship between player profiles, as defined by the Hexad scale, and the use of the ClassCraft platform for learning sustainable mobility concepts. The Hexad scale serves as an instrument to analyse the various motivations exhibited by each student when interacting with the gamified application. Specifically, we examine the connection between player profiles, learning levels, the components of the ClassCraft platform, and the impact of gender on this relationship. An experiment was conducted with 75 fifth-grade primary school students (aged 10–12) who used the ClassCraft platform. Several linear regression models correlated various variables with the player profiles included in the Hexad scale. The results indicate a relationship between player profiles and the variables considered: final score on the platform, number of activities completed, number of connections made, player level achieved, student satisfaction level, and learning levels. Additionally, the high percentage of socialiser profiles found among the students is perfectly in line with some of the intrinsic characteristics of the ClassCraft platform. Furthermore, the analysis revealed minimal differences between male and female players across most profiles.